Regional Regulation Problems in the Field of Salt Industry Development Perspective of Farmers in Sampang Regency - Mukhlis, Mukhlis; Jufri, Muwaffiq; Winata, A. Yahya Surya; Zahid, Ach (Faculty of Law Universitas Trunojoyo Madura, 2024)
Sampang is an area that has the largest salt field in Madura. But the existence of abundant salt fields does not make it a developed region. Sampang has consistently been a disadvantaged area. Thus, predictably, there are various problems regarding salt in Sampang. This issue needs to be studied, especially on legal issues that hinder the development of the salt industry in Sampang. To answer this problem, empirical legal research methods are used to explore and identify legal problems that occur in the field related to salt issues. The results and discussion in this study revealed that there are at least three main problems that hinder the progress of the salt industry perspective of salt farmers in Sampang Regency. The three main problems are the absence of regional regulations on aquaculture, the absence of regional policies that support salt pricing that benefits farmers, and the absence of policies on the implementation of regional duties in the field of providing facilities and infrastructure that support the development of the salt industry in Sampang Regency.